2020
DOI: 10.1111/maps.13560
|View full text |Cite
|
Sign up to set email alerts
|

Abundant extraterrestrial amino acids in the primitive CM carbonaceous chondrite Asuka 12236

Abstract: The Asuka (A)-12236 meteorite has recently been classified as a CM carbonaceous chondrite of petrologic type 3.0/2.9 and is among the most primitive CM meteorites studied to date. Here, we report the concentrations, relative distributions, and enantiomeric ratios of amino acids in water extracts of the A-12236 meteorite and another primitive CM chondrite Elephant Moraine (EET) 96029 (CM2.7) determined by ultra-high-performance liquid chromatography time-of-flight mass spectrometry. EET 96029 was highly deplete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
69
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 45 publications
(75 citation statements)
references
References 150 publications
(228 reference statements)
6
69
0
Order By: Relevance
“…">3.The higher abundances of presolar grains in A12236 and especially A12169 than seen in other CM chondrites provide further strong support to petrographic and chemical evidence (Glavin et al. 2020; Kimura et al. 2020; Noguchi et al.…”
Section: Discussionsupporting
confidence: 60%
See 2 more Smart Citations
“…">3.The higher abundances of presolar grains in A12236 and especially A12169 than seen in other CM chondrites provide further strong support to petrographic and chemical evidence (Glavin et al. 2020; Kimura et al. 2020; Noguchi et al.…”
Section: Discussionsupporting
confidence: 60%
“…More recently, Glavin et al. (2020) found a much higher abundance of amino acids in A12236 than in Paris, providing further support that this meteorite has been less affected by parent‐body alteration than any previously studied CMs.…”
Section: Introductionmentioning
confidence: 67%
See 1 more Smart Citation
“…More specifically, unaltered CM and CR type 3 (petrologic type ≥2.6, see discussion below) carbonaceous chondrites show racemic isovaline, but more aqueously altered type 1 or type 2 carbonaceous chondrites (petrologic type 2.0–2.5, see discussion below) contain l ‐isovaline excesses (Glavin and Dworkin 2009; Glavin et al. 2010, 2020b; Martins et al. 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Although abiotic chemistry should produce racemic mixtures of chiral compounds in the absence of a chiral driving force, enantiomeric excesses of certain amino acids, including isovaline, have been observed in a variety of meteorites. The L-isovaline excesses observed in CB (up to 14%) and CH (up to 20%) chondrites are among the highest reported (Burton et al 2013;Glavin et al 2020). Rosenberg et al (2008) showed that spin-polarized secondary electrons emitted from the photolysis of an iron-nickel magnetic substrate result in chiral selective reactivity of (R)-or (S)-2-butanol.…”
Section: Introductionmentioning
confidence: 96%